HISTORY OF STUDY OF ETHNOGRAPHIC VOCABULARY IN WORLD AND UZBEK LINGUISTICS (Academia Science Repository, 2023)
This article focuses on the implementation of ethnographic research in world and Uzbek linguistics, and its study in folklore, dialect, and ethnocultural aspects is highlighted.